Biohydrogen production from food waste / Osuagwu Chiemeriwo Godday - Osuagwu, Chiemeriwo Godday (2014)
Fossil fuels have often served as the current energy source used for day to day activities by households, industries and transportation sectors. However, its combustion has increased the global issue of greenhouse effect, which in turn has led to global warming. With the continuous rise in global temperatures, the quest for an alternative energy source, which will be environmental friendly, is now inevitable. This study was conducted to provide support that hydrogen can be an alternative energy source. Hence, the study was undertaken to investigate the potentials of food waste substrates such as rice waste, fish waste, vegetable waste and mixed waste, in hydrogen production through anaerobic fermentation. Bio-hydrogen production was performed in lab scale reactors, using 250 mL serum bottles. The food waste was first mixed with the anaerobic sewage sludge and incubated at 37°C for 31 days (acclimatization). The anaerobic sewage sludge was then heat treated at 80°C for 15 minutes. The experiment was conducted at an initial pH of 4.0, 5.5 and 6.0 and temperature of 27°C, 35°C, and 55°C. The maximum cumulative hydrogen produced by rice, fish, vegetable and mixed food waste substrates were highest at 35oC and at pH of 5.5 (Rice =26.97 ± 0.76 mL, fish = 89.70 ± 1.25 mL, vegetable = 42.00±1.76 mL, mixed = 108.90±1.42 mL). A comparative study of acclimatized (the different food waste substrates were mixed with anaerobic sewage sludge and incubated at 37°C for 31days) and non-acclimatized food waste substrate (food waste that was not incubated with anaerobic sewage sludge) revealed that acclimatized food waste substrate enhanced bio-hydrogen production by two fold. This was further verified using a statistical test at (P < 0.001). Using the Gompertz kinetic model, rice waste had the highest hydrogen production potential of 83 mL followed by mixed (74.2 mL), fish (55.80 mL) and vegetable (32.70 mL). However, the model also revealed mixed waste to have the highest rate of hydrogen production of 60 mL/d, followed by rice (41.22 mL/d), fish (30.7 mL/d) and vegetable (16.1 mL/d). Food waste substrates such as rice, fish, vegetable and their combinations are potential substrates for hydrogen production. Addition of metal ion such as Pb ions 5 mg/L, 10 mg/L and 15 mg/L was observed to increase hydrogen production from 10.3 mL to 16.6 mL, 41.6 mL and 42.3 mL respectively. This was also the case in the column experiments where Pb ion concentrations of 5 mg/L, 10 mg/L and 15 mg/L had a maximum hydrogen yield of 42.96 mL, 124.8 mL and 157.95 mL respectively. Thus, Pb ions at these levels enhanced bio-hydrogen production.